Validação e aplicação de método empregando QuEChERS modificado e GC-ECD para determinação de resíduos de pesticidas em grão e casca de arroz - Peixoto, Sandra Cadore (2010)
The current agriculture is characterized by the use of new technologies and equipment, the increased number of agronomic research and the use of a variety of inputs such as pesticides and fertilizers. All this is directly related to human health risks and environmental contamination caused by the intensive use of pesticides. Among the main food consumed by humans, rice is a prominent component. Considering this, it is clear that future research should be increasingly strict about convenience and consequences of pesticide use on crops. In this work a method using extraction by the modified QuEChERS method and quantification by gas chromatography with electron capture detection (GC-ECD) was developed and validated for the determination of residues of the pesticides azoxystrobin, bifenthrin, lambda-cyhalothrin, cypermethrin, difenoconazole, epoxiconazole, parathion-methyl, permethrin, tiamethoxan and trifloxystrobin in rice grain, polished and browm, both in the cooked and raw form, in parboiled raw polished grain and in the rice husk. The method consisted of a modified QuEChERS extraction step using 10 g of rice: water 1:1 (w/w) mixture and husk:water 1:3 (w/w) in which 10 mL of acetonitrile containing 1% (v/v) acetic acid was added, followed by a partition step after adding 3.0 g of anhydrous magnesium sulphate and 1.7 g of sodium acetate. The clean-up step was performed by adding 500 mg of C18 and 600 mg magnesium sulfate. The extracts were analyzed by GC-ECD. To validate the method, detection and quantification limits (LOD and LOQ), linearity, precision and accuracy were determined. The analytical curves showed linearity with coefficients of determination greater than 0.993. The method presented good recovery values between 80 and 120%. The method was considered adequate for analysis of pesticide residues in grain and rice husk. After validation, the method was applied to samples from an experimental field of the UFSM Campus in the harvest 2008-2009. No pesticides residues were found in the studies samples.